Beispiel Nr: 01
$ \text{Gegeben:}\\\text{Oberfläche} \qquad O \qquad [m^{2}] \\ \\\text{Grundfläche} \qquad G \qquad [m^{2}] \\ \\ \text{Gesucht:} \\\text{Mantelfläche} \qquad M \qquad [m^{2}] \\ \\ M = O- G \\ \textbf{Gegeben:} \\ O=44m^{2} \qquad G=5m^{2} \qquad \\ \\ \textbf{Rechnung:} \\ M = O- G \\ O=44m^{2}\\ G=5m^{2}\\ M = 44m^{2}- 5m^{2} \\ M=39m^{2} \\ \small \begin{array}{|l|} \hline O=\\ \hline 44 m^2 \\ \hline 4,4\cdot 10^{3} dm^2 \\ \hline 4,4\cdot 10^{5} cm^2 \\ \hline 4,4\cdot 10^{7} mm^2 \\ \hline 0,44 a \\ \hline 0,0044 ha \\ \hline 4,4\cdot 10^{-5} km^2 \\ \hline \end{array}\\ \small \begin{array}{|l|} \hline G=\\ \hline 5 m^2 \\ \hline 500 dm^2 \\ \hline 5\cdot 10^{4} cm^2 \\ \hline 5\cdot 10^{6} mm^2 \\ \hline 0,05 a \\ \hline 0,0005 ha \\ \hline 5\cdot 10^{-6} km^2 \\ \hline \end{array}\\ \small \begin{array}{|l|} \hline M=\\ \hline 39 m^2 \\ \hline 3,9\cdot 10^{3} dm^2 \\ \hline 3,9\cdot 10^{5} cm^2 \\ \hline 3,9\cdot 10^{7} mm^2 \\ \hline 0,39 a \\ \hline 0,0039 ha \\ \hline 3,9\cdot 10^{-5} km^2 \\ \hline \end{array}\\$